Innovative network pricing to support the transition to a smart grid in a low-carbon economy - Faerber, Laura Antonia; Balta-Ozkan, Nazmiye; Connor, Peter M. (Elsevier, 2018)
This paper outlines how current distribution network pricing can be revised to enable transition to a smart grid in a low-carbon economy. Using insights from expert interviews, it highlights multiple trade-offs between innovative pricing approaches and regulatory principles which might be resolved by a political decision on how the costs should be recovered or socialised. It then identifies four essentials for a successful implementation of a new mechanism: (i) Closer collaboration between TSO and DNO/DSO concerning local dispatch to improve system efficiency. (ii) Installation of smart meters to collect data providing information about the actual contribution to the grid utilisation of each customer. (iii) Intensified cooperation between supplier and DNO/DSO to pass-through the price signal on the electricity bill. (iv) A legislative framework to facilitate data sharing and data management and communication among network stakeholders – essentially a relaxation of current privacy legislation as an enabler for new approaches to network management, and potentially to reduce costs to the consumer. This suggests the focus for future network pricing should be on services and functions provided by the grid rather than on the commodity power itself.
Keywords: Tariff design; Grid utilisation; Cross-subsidisation; Ancillary services; DUoS; Smart grid